2007
DOI: 10.3141/1999-16
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Features and Characteristics of Speed Dispersion in Urban Freeway Traffic

Abstract: Characteristics of speed dispersion in urban freeway traffic are presented. Two definitions of speed dispersion are proposed: the standard deviation of the individual speeds and the average speed difference of two neighboring vehicles. On the basis of the definitions, traffic data obtained from two urban freeways in China are studied, and different characteristics of speed dispersion are found in four substates of traffic flow, which correspond to four regions in the empirical fundamental diagram. In the bunch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 16 publications
4
27
1
Order By: Relevance
“…First, CVS ranged from 10% to 35% northbound and 10% to 55% southbound. The CVS range of the northbound is close to the observation by Wang et al (2007) from 7% to 32%, but that of the southbound is broader than the proposal by May (1990) from 0 to 1 ffiffi S p , which implies that time mean speed is within 1 mph greater than space mean speed. In fact, Rakha and Zhang (2005) indicated that large differences between these two mean speeds, from 10% to 30%, are not uncommon when traffic is congested.…”
Section: Data Validitysupporting
confidence: 67%
See 3 more Smart Citations
“…First, CVS ranged from 10% to 35% northbound and 10% to 55% southbound. The CVS range of the northbound is close to the observation by Wang et al (2007) from 7% to 32%, but that of the southbound is broader than the proposal by May (1990) from 0 to 1 ffiffi S p , which implies that time mean speed is within 1 mph greater than space mean speed. In fact, Rakha and Zhang (2005) indicated that large differences between these two mean speeds, from 10% to 30%, are not uncommon when traffic is congested.…”
Section: Data Validitysupporting
confidence: 67%
“…Another 'complicated' form between speed and SDS may be expected, as shown in Equation (7) derived from Equation (5). Finally, although Wang et al (2007) proposed flow as an exponential form of SDS, we do not have similar findings but expect, through the relationship between flow and CVS, that flow and speed can jointly explain SDS to a certain degree.…”
Section: Sds Vs Occupancy Speed and Flowcontrasting
confidence: 46%
See 2 more Smart Citations
“…The traffic flow on freeways is described traditionally in term of three parameters: the mean speed, the traffic flow rate, and the traffic density, and the relationship between flow rate and traffic density can form a curve called the fundamental diagram for traffic flow. In order to study the relationships between the three traffic parameters and speed dispersion, traffic data were obtained by video-tapping from Lukou airport freeway, Nanjing, Jiangsu province, Wang et al (2007). The site data collected from is a 5 km segment between two ramps in Lukou airport freeway, instrumented with video cameras every two kilometers each side, and the traffic data collected from station 3 during the period from 14:34 to17:37 on July 3, from 07:40 to 10:45 on July 6, and from 16:32 to 17:50 on July 11, 2007 were utilized in our study.…”
Section: Detect Outlier From Multi-dimensional Traffic Flow Datamentioning
confidence: 99%